2014
DOI: 10.3390/polym6071897
|View full text |Cite
|
Sign up to set email alerts
|

Salt Effect on Osmotic Pressure of Polyelectrolyte Solutions: Simulation Study

Abstract: Abstract:We present results of the hybrid Monte Carlo/molecular dynamics simulations of the osmotic pressure of salt solutions of polyelectrolytes. In our simulations, we used a coarse-grained representation of polyelectrolyte chains, counterions and salt ions. During simulation runs, we alternate Monte Carlo and molecular dynamics simulation steps. Monte Carlo steps were used to perform small ion exchange between simulation box containing salt ions (salt reservoir) and simulation box with polyelectrolyte chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
(127 reference statements)
2
19
0
Order By: Relevance
“…Sodium is responsible for maintaining basic vital functions. It is involved in maintaining water and electrolyte balance [ 120 ], acid-base [ 121 ], osmotic pressure [ 122 ], transport of amino acids, carbohydrates and vitamins [ 123 ] serotonin (SERT), dopamine, noradrenaline, GABA [ 124 , 125 ], excitability neuromuscular [ 126 ], and conduction of nerve impulses [ 127 ]. Physiological sodium levels in the plasma range from 135 to 145 mM/L ( Table 3 ).…”
Section: Sodium Deficitmentioning
confidence: 99%
“…Sodium is responsible for maintaining basic vital functions. It is involved in maintaining water and electrolyte balance [ 120 ], acid-base [ 121 ], osmotic pressure [ 122 ], transport of amino acids, carbohydrates and vitamins [ 123 ] serotonin (SERT), dopamine, noradrenaline, GABA [ 124 , 125 ], excitability neuromuscular [ 126 ], and conduction of nerve impulses [ 127 ]. Physiological sodium levels in the plasma range from 135 to 145 mM/L ( Table 3 ).…”
Section: Sodium Deficitmentioning
confidence: 99%
“…The net result of the Gibbs-Donnan effect is that more water moves into the extrafibrillar compartment than would be predicted on the basis of oncotic pressure of the PAH molecules alone. Partitioning of osmotically-active counterions and salt ions across membrane impermeable to polyelectrolyte chains to establish Gibbs-Donnan equilibrium 36 has been exhaustively modelled using Monte Carlo simulations 37 .…”
Section: Establishment Of Gibbs-donnan Equilibriummentioning
confidence: 99%
“…For instance, at 1M ionic strength for PAMAMPS, we can evaluate from the work of Trizac et al [ 44 ] a shift of ξ * from unity (Manning) to ~0.65. Moreover, Carrillo et al [ 45 ] showed using hybrid Monte-Carlo/molecular dynamics simulations that the fraction of condensed counter-ions decreases with increasing ionic strength, while Muthukumar [ 46 ] predicted an opposite behavior. Due to the complexity of the counter-ions condensation phenomenon, which depends on many physico-chemical parameters (ionic strength, polymer concentration, polymer backbone size, charge density parameter), we restricted our estimation to the framework of Manning theory.…”
Section: Theoretical Sectionmentioning
confidence: 99%